2015
DOI: 10.1523/jneurosci.4051-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Synaptic Inhibition Declines during Auditory Learning

Abstract: Auditory learning is associated with an enhanced representation of acoustic cues in primary auditory cortex, and modulation of inhibitory strength is causally involved in learning. If this inhibitory plasticity is associated with task learning and improvement, its expression should emerge and persist until task proficiency is achieved. We tested this idea by measuring changes to cortical inhibitory synaptic transmission as adult gerbils progressed through the process of associative learning and perceptual impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 66 publications
2
24
0
Order By: Relevance
“…Further studies confirmed the recruitment of layer II/III interneurons in auditory fear memory in mice (Pi et al 2013;Sarro et al 2015) Changes in neuronal activity have also been detected in superficial layers during spatial (Maviel et al 2004) and other hippocampal-dependent (Frankland et al 2004;Lesburguères et al 2011) tasks in both rats and mice brain cortices, including the prefrontal, anterior cingulate, parietal and temporal cortices (Frankland and Bontempi 2005). Spine remodeling and growth has been shown to occur in superficial layers during remote memory formation in mice (Lesburguères et al 2011;Vetere et al 2011;Xie et al 2014), and contextual fear conditioning has been shown to determine a memory-related activation of sparse neurons in layer II of several cortices in mice, which lasts for 2 months (Xie et al 2014).…”
Section: Layer-specific Memory Evoked Activity In the Te2 Cortexmentioning
confidence: 67%
“…Further studies confirmed the recruitment of layer II/III interneurons in auditory fear memory in mice (Pi et al 2013;Sarro et al 2015) Changes in neuronal activity have also been detected in superficial layers during spatial (Maviel et al 2004) and other hippocampal-dependent (Frankland et al 2004;Lesburguères et al 2011) tasks in both rats and mice brain cortices, including the prefrontal, anterior cingulate, parietal and temporal cortices (Frankland and Bontempi 2005). Spine remodeling and growth has been shown to occur in superficial layers during remote memory formation in mice (Lesburguères et al 2011;Vetere et al 2011;Xie et al 2014), and contextual fear conditioning has been shown to determine a memory-related activation of sparse neurons in layer II of several cortices in mice, which lasts for 2 months (Xie et al 2014).…”
Section: Layer-specific Memory Evoked Activity In the Te2 Cortexmentioning
confidence: 67%
“…AM detection was assessed with an aversive conditioning paradigm as described previously (29,87,88). Psychometric functions were fit with cumulative Gaussians and transformed to the signal detection metric, d′ (89).…”
Section: Methodsmentioning
confidence: 99%
“…The neural basis of PL has commonly been evaluated by focusing on two time points (pre-vs. posttraining) or groups (trained vs. untrained) (6-12, 14-16, 30). However, training-based perceptual improvement can be associated with transient phases of functional plasticity, even within a single network (26)(27)(28)(29). Thus, studies that are restricted to one or two time points could fail to identify a temporary contribution of a particular brain region to PL.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…For CHL animals, identical stimuli were used however they were presented at 95 dB SPL (i.e., 45 dB louder than that used for NH animals), to compensate for the induced loss. Except for the sound level used for CHL animals, all general training and testing procedures were similar to those described previously for NH animals (Buran et al, 2014b; Sarro et al, 2015). …”
Section: Experimental Approachesmentioning
confidence: 99%